A Retrospective Cohort Study of Lesion Distribution of HIV-1 Infection Patients With Cryptococcal Meningoencephalitis on MRI: Correlation With Immunity and Immune Reconstitution. Issue 6 (February 2016) - Xia, Shuang; Li, Xueqin; Shi, Yanbin; Liu, Jinxin; Zhang, Mengjie; Gu, Tenghui; Pan, Shinong; Song, Liucun; Xu, Jinsheng; Sun, Yan; Zhao, Qingxia; Lu, Zhiyan; et al.
Abstract : Abstract: The objective of this paper is to correlate the MRI distribution of cryptococcal meningoencephalitis in HIV-1 infection patients with CD4 T cell count and immune reconstitution effect. A large retrospective cohort study of HIV patients from multi-HIV centers in China was studied to demonstrate the MRI distribution of cryptococcal meningoencephalitis and its correlation with the different immune status. The consecutive clinical and neuroimaging data of 55 HIV-1-infected patients with cryptococcal meningoencephalitis collected at multi-HIV centers in China during the years of 2011 to 2014 was retrospectively analyzed. The enrolled patients were divided into 2 groups based on the distribution of lesions. One group of patients had their lesions at the central brain (group 1, n = 34) and the other group of patients had their lesions at the superficial brain (group 2, n = 21). We explored their MRI characterization of brain. In addition, we also compared their CD4 T cell counts and immune reconstitution effects between the 2 groups based on the imaging findings. No statistical difference was found in terms of age and gender between the 2 groups. The medians of CD4 T cell counts were 11.67 cells/mm 3 (3.00–52.00 cells/mm 3 ) in group 1 and 42.00 cells/mm 3 (10.00–252.00 cells/mm 3 ) in group 2. Statistical difference of CD4 T cell count was found between the 2 groups ( P = 0.023). Thirteen patients in group 1 (13/34) and 12 patients in group 2 (12/21) received highly active antiretroviral treatment (HAART). Patients of group 2 received HAART therapy more frequently than patients of group 1 ( P = 0.021). Central and superficial brain lesions detected by MR imaging in HIV-1-infected patients with cryptococcal meningoencephalitis are in correlation with the host immunity and HAART therapy.